Dispersal and coexistence of two non-native crayfish species (Pacifastacus leniusculus and Procambarus clarkii ) in NE Portugal over a 10-year period - Bernardo, J.M. (2012)
NE Portugal is one of the most isolated and low populated regions of Western Europe. Recently, two American crayfish species reached this area: signal crayfish Pacifastacus leniusculus coming from Spain and red swamp crayfish Procambarus clarkii in its northward expansion. The dispersion of both species was followed throughout the last decade in river Maçãs (Douro catchment). Our results support the hypothesis of faster downstream colonisation. The mean spread rate of signal crayfish was faster for the downstream expansion, 2.8 km·yr-1, while the upstream rate was 1.7 km·yr-1. Exceptionally, in one period, the rate of spread reached 6.7 km·yr-1, which was apparently caused by downstream washing in extreme conditions of flow. The mean rate of spread is higher than the observed in other studies which may also be related to the low current velocity of late spring and summer that provides favourable conditions for a fast upstream colonisation. Coexistence of signal and red swamp crayfish was detected in a large river sector. Signal crayfish strongly dominates in the upper and intermediate sectors which are the colder part of the river and in the lower sectors, species abundances are not significantly different. Winter temperature in the higher altitude reaches seems to moderate the competitive abilities of P. clarkii.